2007
DOI: 10.21236/ada473125
|View full text |Cite
|
Sign up to set email alerts
|

Super Resolution Imaging Applied to Scientific Images

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…High-frequency information is important for constructing important edges in the high-resolution approximation. Evidently, this leads to the development of Super Resolution (SR) algorithms [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] which synthesize missing high-resolution pixel information that is not explicitly found in the LR measurements. SISR methods have been widely advanced by the breakthroughs in deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency information is important for constructing important edges in the high-resolution approximation. Evidently, this leads to the development of Super Resolution (SR) algorithms [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] which synthesize missing high-resolution pixel information that is not explicitly found in the LR measurements. SISR methods have been widely advanced by the breakthroughs in deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…SR studies started before deep learning [34]. Advances in deep learning have affected SR studies and successful results have been observed [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Super-resolution techniques have revolutionized many fields such as biology, chemistry, and medicine, by enabling study on the order of a few nanometers [1][2][3]. These techniques overcome the inherent restriction of the diffraction limit due to the loss of evanescent waves that carry sub-wavelength information.…”
Section: Introductionmentioning
confidence: 99%